2022
DOI: 10.1111/cge.14119
|View full text |Cite
|
Sign up to set email alerts
|

Kidney failure in BardetBiedl syndrome

Abstract: The aim of this study was to explore kidney failure (KF) in Bardet–Biedl syndrome (BBS), focusing on high‐risk gene variants, demographics, and morbidity. We employed the Clinical Registry Investigating BBS (CRIBBS) to identify 44 (7.2%) individuals with KF out of 607 subjects. Molecularly confirmed BBS was identified in 37 KF subjects and 364 CRIBBS registrants. KF was concomitant with recessive causal variants in 12 genes, with BBS10 the most predominant causal gene (26.6%), while disease penetrance was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 78 publications
4
19
0
Order By: Relevance
“…49 Recently, using CRIBBS registry, Meyer et al identified Eagle Barrett syndrome in four children. 50 Reproduction is difficult but some patients gave birth to children.…”
Section: Hypogonadism and Genitourinary Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Recently, using CRIBBS registry, Meyer et al identified Eagle Barrett syndrome in four children. 50 Reproduction is difficult but some patients gave birth to children.…”
Section: Hypogonadism and Genitourinary Abnormalitiesmentioning
confidence: 99%
“…[69][70][71][72] Currently, thanks to the progress in genetics, twenty-six genes have been associated with the syndrome, an increasing number over years (Table 2). 50 However, mutations in BBS1 to BBS18 account for about 70-80% of cases worldwide 73 and about 50% of diagnosis in the western countries are due to mutations in three genes: BBS1, BBS2 and BBS10. 19,74 In Caucasian populations, indeed, mutations in BBS1 and BBS10 are detected in 21-30% of patients, 75 a percentage rising to 40-50% in Northern European patients.…”
Section: Genetics Of Bbs and Genotype-to-phenotype Correlationmentioning
confidence: 99%
“…Several minor features have also been documented in individuals with BBS, including facial dysmorphism, developmental delay, speech deficit, neurological abnormalities, metabolic and endocrine disturbance, diabetes mellitus, cardiovascular defects and Hirschsprung disease (Branfield Day et al, 2016; Olson et al, 2019). Assembly and analysis of consistent and longitudinal clinical data from the Clinical Registry Investigating Bardet‐Biedl Syndrome (CRIBBS), have refined further the incidence and variability of clinical phenotypes (Meyer et al, 2022; Pomeroy, Krentz, et al, 2021; Pomeroy, VanWormer, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Assembly and analysis of consistent and longitudinal clinical data from the Clinical Registry Investigating Bardet-Biedl Syndrome (CRIBBS), have refined further the incidence and variability of clinical phenotypes (Meyer et al, 2022;Pomeroy, Krentz, et al, 2021;.…”
mentioning
confidence: 99%
“…NPH is characterized by smaller, hyperechogenic kidneys with cortico-medullary cysts and poor cortico-medullary differentiation, tubular atrophy, disintegration, and irregular thickening of the tubular basement membrane, leading to fibrotic kidneys with shrunken appearance 18 . Similarly, JS and JATD patients commonly display abnormal congenital kidney developmental phenotypes such as dysplastic, fibrocystic kidneys and reach ESKD within childhood or adolescence 19,20 . So far, ciliopathies have been linked to mutations in ~ 200 genes 6,7 , a significant number of which encode centrosomal proteins, and many of these mutations result in congenital kidney developmental defects and early-onset fibrocystic disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%